2014
DOI: 10.1080/10408398.2012.678421
|View full text |Cite
|
Sign up to set email alerts
|

BPA, an Energy Balance Disruptor

Abstract: Bisphenol A (BPA) is used extensively in the world and is present in a diverse range of manufactured articles including dental resins, polycarbonate plastics, and the inner coating of food cans. It is a high volume chemical, with global production at 3.6 × 10(9) kg per year. BPA was identified as a high priority for assessment of human health risk because it was considered to present greatest potential for human exposure. Most studies of the health effects of BPA have focused on endocrine disruption leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 85 publications
0
32
0
1
Order By: Relevance
“…Based on the EC 50 values, BPA was only one to two orders of the magnitude (10e100 fold) less toxic than highly cytotoxic drug Doxorubicin ® and 30e300 fold more toxic compared to Aspirin ® (Table 3). Numerous the in vitro (Hanioka et al, 2008;Le Corre et al, 2013) and the in vivo studies (Komada et al, 2014;Song et al, 2014) reported that BPA had adverse effects at lower concentrations than it was in the no observed adverse effect levels (NOAELs) of 5e50 mg/kg/day, established in the regulatory toxicity studies that are used for human risk assessment (FitzGerald and Wilks, 2014). Qian et al (2014) provided the insight into the BPAinduced reproductive toxicity in mouse Sertoli cell line TM4.…”
Section: In Vitro Toxicity In Mammalian Cell Linesmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on the EC 50 values, BPA was only one to two orders of the magnitude (10e100 fold) less toxic than highly cytotoxic drug Doxorubicin ® and 30e300 fold more toxic compared to Aspirin ® (Table 3). Numerous the in vitro (Hanioka et al, 2008;Le Corre et al, 2013) and the in vivo studies (Komada et al, 2014;Song et al, 2014) reported that BPA had adverse effects at lower concentrations than it was in the no observed adverse effect levels (NOAELs) of 5e50 mg/kg/day, established in the regulatory toxicity studies that are used for human risk assessment (FitzGerald and Wilks, 2014). Qian et al (2014) provided the insight into the BPAinduced reproductive toxicity in mouse Sertoli cell line TM4.…”
Section: In Vitro Toxicity In Mammalian Cell Linesmentioning
confidence: 98%
“…The presence of this environmental estrogen is associated with a range of adverse health effects such as fertility disorders (decrease in sperm production), obesity, especially in children and adolescents (Trasande et al, 2012), disrupted pancreatic b-cell function, disrupted thyroid hormone function (Le Corre et al, 2013), cardiovascular disorders and increased carcinogenic risk (Rubin, 2011). Recent studies have also reported liver damage effects (Le Corre et al, 2013) and adverse findings in animals (Song et al, 2014) suggesting that, beside the endocrine disrupting and obesogenic properties, BPA also possesses toxic effects. New data on BPA toxicity demonstrate that human organism is more susceptible to its toxicity than the rodents and the renewed estimation of the BPA safety dose is indispensable (Rubin, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Actually, food, and especially canned food, is considered the predominant source of contamination from BPs, mainly from BPA (Le Corre et al, 2015). Due to its large number of applications, BPA is ubiquitously present in the environment so that human exposure routes are multiple.…”
Section: Introductionmentioning
confidence: 99%
“…EDCs are substances that influence synthesis, transport, secretion, action, binding or elimination of natural hormones in the body (García-Arevalo et al, 2014;Jeng, 2014;Le Corre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%